Evaluating the degree of difficulty of laparoscopic colorectal surgery - Dimassi, Hani (2008)
The introduction of laparoscopy has brought about great progress in current surgical practices. The benefits to patients, families, employers, and hospitals have been significant. The indications for laparoscopic surgery have gradually expanded over time as surgeons have gained more experience, with many laparoscopic procedures becoming standard practice.1- 4 The use of laparoscopic techniques in the field of colorectal surgery followed soon after the early success of laparoscopic cholecystectomy, with the first case reports published in 1991.5,6 Laparoscopy for colorectal surgery, however, has not been as readily embraced into surgical practice as other procedures, partly because of the requirement for advanced laparoscopic surgical skills and partly because of initial concerns about potential risks of tumor dissemination in malignant neoplasms. These concerns have now been addressed in randomized controlled trials that have shown that the laparoscopic approach is associated with the same significant short-term benefits without a compromise in oncological long-term outcomes.7- 10 It is therefore anticipated that there will be an increased demand for laparoscopic colorectal procedures in the future, with many surgeons entering this field. The purpose of this study is to quantify the degree of difficulty involved in the performance of various laparoscopic colorectal procedures. It aims to elucidate the specific difficulties that are likely to be encountered by breaking down each surgical procedure into its key elements. This will provide a guide for surgeons who are learning these operations so they can choose appropriately which procedures to perform first and anticipate and prepare for the difficulties they are likely to encounter. It is hoped that proper case selection based on this data will result in a lower conversion rate, thereby benefiting patients and reducing operative times and costs.